(untitled) (Computer systems and information technologies, 2022)
The research of methods of energy efficiency management in the "Smart Home" system is carried out in the work. For researchers and practitioners, the problem of monitoring, estimating and reducing energy consumption by homes is an urgent task. According to the results of research, the method of determining user preferences has been improved, which has allowed to achieve more efficient use of energy. The method has also been further developed, which provides the ability to determine the number of people in the room and helps control oxygen levels.